Natural Radiation Shielding on Mars Measured With the MSL/RAD Instrument. Issue 8 (20th August 2021) - Ehresmann, B.; Hassler, D. M.; Zeitlin, C.; Guo, J.; Wimmer‐Schweingruber, R. F.; Khaksari, S.; Loeffler, S.
Abstract: Protecting astronauts from the effects of space radiation remains one major stepping stone for the exploration of Mars. Long‐term exposure to radiation can lead to severe health effects and affects allowable mission duration. Mission designs for Mars include the use of radiation shelters that provide additional mass to surround the astronauts. This leads to incoming radiation losing energy through ionization processes. This is important during solar energetic particle events when solar protons can reach the surface with high intensities. Additionally, shelters provide a long‐term reduction of the exposure to galactic cosmic rays. As mass is an important time and cost factor in space travel, using natural sheltering already on Mars is a desirable option. One candidate is to use subterranean lava tubes that provide shelter from the radiation from above. Other options include craters, cliff walls, or rock overhangs. Here, we present the first in situ measurements of radiation sheltering by natural environments on the surface of Mars. The data were acquired with the Radiation Assessment Detector (RAD) on board the Curiosity rover in Gale crater on Mars. We show measurements from when Curiosity was parked close to Butte M12 in the Murray Buttes formation, which blocked out 19% of the surrounding sky view. During this time, from Mars Science Laboratory (MSL) sol 1456–1467, we find a decrease of 4% in the expected dose rate, and a decrease of 7.5% in the neutral particle environment. This proof of principle is an important step to validate plans to use natural sheltering on Mars. Plain Language Summary: Protecting astronauts on Mars from the exposure to space radiation remains one of the major challenges for the human exploration of the red planet. A viable option for this is to provide the astronauts with a radiation shelter that surrounds the astronauts with enough mass and material to reduce the effects of radiation. Since bringing additional material from Earth to Mars is extremely time and cost prohibitive, making use of natural terrain and rocks on Mars would theoretically be ideal for this purpose. Here, we present the first‐ever measurements taken on Mars with the Radiation Assessment Detector (RAD) that prove that natural terrain provides such radiation protection. While NASA's Curiosity rover was parked up close to a butte for 12 days, RAD measured a distinct decrease in radiation dose. This was due to the butte blocking out part of the sky and, thus, shielding the rover from the space radiation coming from the direction of the butte. Key Points: We present the first in situ measured proof of principle of radiation sheltering by natural terrain on the surface of Mars We find that a Martian butte, blocking out 19% of the sky, decreases the radiation dose measured by Mars Science Laboratory (MSL)/Radiation Assessment Detector (RAD) by 4% We find that the Martian surface neutral radiation environment also decreases by 7.5% due to the sheltering provided by the butte